Association between Outcome of severe traumatic brain injury and demographic, clinical, injury-related variables of patients - Marzieh Ziaeirad; Nasrollah Alimohammadi; Alireza Irajpour; Bahram Aminmansour (Wolters Kluwer Medknow Publications, 2018)
Background: Traumatic brain injury (TBI) is a main health problem among communities. There exists a variety of effective factors on the outcome of patients with TBI. We describe the demographic, clinical, and injury related variables of the patients with severe TBI, and determine the predictors of outcome. Materials and Methods: We did this cross-sectional study on all 267 adult patients with severe TBI admitted to three trauma centers of Isfahan University of Medical Sciences (IUMS) from March 20, 2014 to March 19, 2015. Data were extracted from patients' profiles. We considered the patients' outcome as discharged and died. We analyzed the collected data using descriptive (frequency, mean, and standard deviation) and analytical (independent t-test, Mann-Whitney U-test, Kruskal-Wallis test and logistic regression) statistics in Statistical Package for the Social Sciences (SPSS) 16.0. We considered p < 0.05 as the significance level. Results: The mean (SD) age of patients was 43.86 (18.40) years. The majority of the population was men (87.27%). Road traffic accidents (RTAs) were the most common mechanism of trauma (79.40%). The mean (SD) of Glasgow coma scale (GCS) was 6.03 (3.11). In 50.19% of the patients, the pupillary reflex was absent. One hundred and twenty-four patients (46.44%) died before discharge. We found age, gender, GCS, pupillary reflex, hypernatremia, and increased intracranial pressure (IICP) as the predictors of death in severe TBI. Conclusions: In this study, the mortality rate of patients with severe TBI was high. In addition, some factors were determined as the significant predictors of outcome. The findings can assist in planning to enhance the quality of care and reduce the mortality rate in the patients with severe TBI.